Sheet Pile Failure Caused by Scouring and Sand Mining at Padang River Bank - Hansen Tananda; Andy Sugianto; Paulus Pramono Rahardjo (Himpunan Ahli Teknik Tanah Indonesia, 2023)
Ground movement occurred on the banks of the river in Padang which has been protected by steel sheetpile which borders the Factory property. Indications of ground movement are detected through visual observations. It was also reported that the day before the incident there had been continuous rain until the next day. Based on the results of the technical drilling, it appears that the soil density becomes lower after 10m depth. There is a layer of sandy silt with a soft to medium consistency at a depth of about 18m to 26m. With soil conditions that are dominated by sandy soil, the risk of scouring due to river flow is one of the things that needs to be considered. Landslides occur gradually because changes in river flow patterns gradually changed due to internal and external factors. Internal factors are caused by the flow and behavior of the river itself, while external factors are the activity of mining of sand material around the riverbanks. Along with the swift river flow, especially during flood water conditions, the layers of soil material move and are washed away by the flow of water so that there is a gap between the sheetpile and the original soil. These conditions cause the passive resistance of the sheet pile to gradually decrease and to experience deformation due to the pushing of the soil material that has experienced a movement. Important findings in the investigation is that the very soft clay layer underneath the sandy layers was not detected prior to the investigation.